Pentingnya Diversifikasi dalam Meningkatkan Regulasi Sebuah Bisnis - Aldi Dwi Prasetyo; Dodit Cahyo Nugroho (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
In an era of increasingly complex business competition, diversification has become a crucial strategy, not only aimed at expanding markets but also strengthening internal company regulations. This study aims to explore the relationship between diversification strategies and improving the quality of internal governance in the small and medium enterprise (SME) sector. Using a descriptive qualitative approach, data were collected through non-participant observation, documentation, and netnography of SMEs diversifying their products and services. The results show that diversification encourages businesses to gradually build more orderly management systems, from financial recording and inventory management to internal organizational structures. Furthermore, the adoption of digital technology in the diversification process also accelerates the development of more adaptive internal regulations. This study concludes that diversification plays a crucial role in managerial learning and improving internal business systems. Therefore, it needs to be strategically planned so that its benefits are not limited to market expansion but also to sustainability and improved business governance.